2016
DOI: 10.1371/journal.pone.0155203
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Depletion in Pregnancy Decreases Survival Time, Oxygen Saturation, Lung Weight and Body Weight in Preterm Rat Offspring

Abstract: Animal studies suggest a role of vitamin D in fetal lung development although not studied in preterm animals. We tested the hypothesis that vitamin D depletion aggravates respiratory insufficiency in preterm rat offspring. Furthermore, the effects of vitamin D depletion on growth and lung surfactant were investigated. Female Sprague-Dawley rats were randomly assigned low vitamin D (VDL) or control diet before mating and followed with serum 25-hydroxyvitamin D (s-25(OH)D) determinations. After cesarean section … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 66 publications
4
8
0
Order By: Relevance
“…The animal models were used to compare two groups with different doses: a diet group ( n =18) (<5 IU/kg cholecalciferol) and a control diet group ( n =16) (1500 IU/kg cholecalciferol). This study confirmed the association between vitamin D depletion and respiratory insufficiency in preterm neonates [ 27 ].…”
Section: Animal Studies On the Roles Of Vitamin D In Lung Developmsupporting
confidence: 88%
“…The animal models were used to compare two groups with different doses: a diet group ( n =18) (<5 IU/kg cholecalciferol) and a control diet group ( n =16) (1500 IU/kg cholecalciferol). This study confirmed the association between vitamin D depletion and respiratory insufficiency in preterm neonates [ 27 ].…”
Section: Animal Studies On the Roles Of Vitamin D In Lung Developmsupporting
confidence: 88%
“…Mouse fetal pulmonary SP-D expression increases with advancing gestation, and levels predominantly elevate shortly before birth, stimulated by vascular endothelial growth factor signaling and glucocorticoid treatment ( 54 , 66 69 , 71 , 315 , 316 ). Pulmonary SP-D expression is therefore very low in experimental prematurity ( 317 ); however, various studies of the Sftpd −/− lung phenotype do not support a role for SP-D in normal fetal or postnatal lung development, although the vast accumulation of phospholipids in the Sftpd −/− lung have effects on surfactant homeostasis. Rather, these studies support a role for SP-D in emphysema and fibrosis development during airway remodeling processes later in life, as recently reviewed by Bersani et al ( 318 ).…”
Section: The Role Of Sp-d In Respiratory Diseasementioning
confidence: 99%
“… 60 , 61 Experimental animal models have also strongly suggested vitamin D deficiency as a potential mechanism of placental dysfunction 62 , 63 and respiratory maturation. 64 …”
Section: Vitamin D Metabolism During Pregnancy When Compared With Thementioning
confidence: 99%